Prostate SBRT: Comparison the Efficacy and Toxicity of Two Different Dose Fractionation Schedules - Fuller, Donald Blake; Naitoh, John; Shirazi, Reza; Crabtree, Tami; Mardirossian, George (Frontiers in Oncology, 2020)
BACKGROUND: CyberKnife SBRT is capable of producing dosimetry comparable to that created by HDR brachytherapy. Our original CyberKnife prostate SBRT schedule of 3,800 cGy/4 fractions ("high dose") was based upon favorable published prostate HDR brachytherapy experience. Subsequently, our trial was modified to allow a lower dose of 3,400 cGy/5 fractions ("moderate dose") in selected cases. METHODS: 289 low and intermediate-risk patients were treated to either high dose (178 pts) or moderate dose (111 pts). The dose selection was individualized; high dose more commonly used in younger, intermediate-risk patients and moderate dose more commonly used in older, low-risk patients. RESULTS: Median PSA reached 5-year nadir levels of 0.034 ng/mL in the high dose, versus 0.1 ng/mL in the moderate dose groups, respectively, (p=0.044 by year 4), with 62% vs 44% reaching an ablation PSA nadir by year 5. 5 year biochemical relapse free survival rates measured 98.3% for moderate dose and 94.3% for high dose groups, respectively (p=.1946). 5-year actuarial grade 2 genitourinary (GU) toxicity rates measured 11.6% versus 8.7% for high dose versus moderate dose groups, respectively, with a far lower incidence of grade >=3 GU and grade >=2 GI toxicity rates in both groups. CONCLUSIONS: Both regimens are efficacious in their respective, selected groups. Both arms have low grade >=3 GU toxicity and >=grade 2 GI toxicity. In favor of the original high dose regimen, it has longer follow-up, produces a lower PSA nadir value and is more likely to eventually produce an ablation PSA nadir (<0.1 ng/mL). In favor of the lower dose regimen, it also produces a low PSA nadir, and does so with a slightly lower grade 2 GU toxicity rate. As a lower PSA nadir could be the initial predictor a lower clinical relapse rate far beyond 5 years, even if no difference is apparent within that time frame, a practical strategy could be to more strongly consider the high dose regimen in those with the greatest potential longevity, while for those with a more limited longevity, particularly if they have minimal negative prognostic factors, the moderate dose regimen could be more attractive.